2021
DOI: 10.2147/cmar.s299563
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Radiotherapy Pattern on the Prognosis of Stage IV Lung Adenocarcinomas Harboring EGFR Mutations

Abstract: Introduction The aim of this study was to investigate the role of local radiotherapy in the management of epidermal growth factor receptor (EGFR)-mutant non-small cell lung cancers (NSCLCs) treated with EGFR tyrosine kinase inhibitors (TKIs). Materials and Methods Patients with stage IV EGFR-mutant NSCLC treated with radiotherapy concomitant to EGFR TKIs from May 2010 to December 2017 were retrospectively identified. Overall survival (OS) was the primary endpoints of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Some clinical studies have shown that EGFR TKIs combined with thoracic radiotherapy for advanced NSCLCs with EGFR mutation provides long-term control of primary lung tumors [6][7][8]. Our previous study also confirmed that thoracic radiotherapy was associated with prolonged median OS for this subpopulation patients [9].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Some clinical studies have shown that EGFR TKIs combined with thoracic radiotherapy for advanced NSCLCs with EGFR mutation provides long-term control of primary lung tumors [6][7][8]. Our previous study also confirmed that thoracic radiotherapy was associated with prolonged median OS for this subpopulation patients [9].…”
Section: Introductionsupporting
confidence: 82%
“…This study showed that the mOS of all patients who received thoracic radiotherapy was 36.9 months. The OS of the patients was significantly prolonged as compared to those reported in previous studies, indicating that thoracic radiotherapy could significantly improve the prognosis of lung adenocarcinoma patients with EGFR mutation [ 9 ]. As a local treatment, thoracic radiotherapy could improve the disease conditions of advanced lung adenocarcinoma patients with EGFR mutation [ 17 ].…”
Section: Discussionmentioning
confidence: 80%
“…For the advanced NSCLC, the value of thoracic radiotherapy in the patients with EGFR mutant lung adenocarcinoma for the OS of patients has been previously investigated. The results showed that the patients, receiving thoracic radiotherapy had longer OS than those, who did not receive thoracic radiotherapy [ 18 ]. However, the effects of different radiotherapy dose schemes on the patients’ OS rates are needed to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome data were from our most recent advancement and improvement in early detection, prevention, improved surgical procedures, neoadjuvant therapy, immunotherapy, and targeted therapy. To date, treatment of NSCLC is dependent on the stage of disease at diagnosis, and early-staged NSCLC could be surgically cured, whereas the advanced staged diseases can only be subjected to chemotherapy, radiation therapy, immunotherapy, and/or targeted therapy (Maconachie et al, 2019;Planchard et al, 2018) and their prognosis is, therefore, still poor, approximately less than 5-7% at the best according to the American Cancer Society data (https://www.cancer.org/cancer/ lung-cancer/detection-diagnosis-staging/survival-rates.html) or after advanced therapy (Zhang et al, 2021). Thus, the search and development of biomarkers for early detection and prediction of prognosis and treatment outcome are urgently needed to effectively conquer this now deadly disease clinically.…”
Section: Introductionmentioning
confidence: 99%